Exploring the Chemical Properties and Mechanisms of Herbal Remedies in Moringa, and Ginger in Managing Chronic Diseases: Review - Abubakar, Musa Yahaya; Mathew, Twan Sale; Adam, Ansar Bilyaminu; Ahmad, Kabiru Bashir; Ataitiya, Hylalibiya; Kaugama, Aminu Ado (African Journal of Biochemistry and Molecular Biology Research, 2024)
Herbal remedies have been used for centuries to treat various ailments. Natural products, derived from plants, animals, and microorganisms, have been used for centuries as a source of medicinal compounds in traditional and modern herbal remedies. Understanding the chemical properties and mechanisms of action of these remedies is crucial for their effective and safe application in managing chronic diseases. This review explores the effectiveness of herbal remedies in managing chronic diseases such as diabetes, cardiovascular diseases, and autoimmune disorders. It emphasizes the need for a balanced approach combining herbal and conventional medicine, reducing healthcare costs and improving patient outcomes. The review includes 10 studies investigating the efficacy of herbal remedies in managing chronic diseases in Moringa and Ginger. Moringa, a valuable plant in traditional and modern medicine, has diverse therapeutic effects, making it beneficial for managing chronic diseases. Ginger, a powerful herbal remedy with bioactive compounds like gingerols, shogaols, zingerone, and paradols, is also considered a powerful natural treatment due to its antioxidant, anti-inflammatory, antimicrobial, antiemetic, and anticancer activities. Understanding the chemical properties and mechanisms of action of these remedies can help develop effective treatments for chronic diseases and enhance their integration into modern medicine.